Are ARBs now first‐line therapy for hypertension?. Issue 17 (9th September 2013) - McInnes, Gordon
Abstract: Now that generic ARBs are available and ACE inhibitors have consequently lost their cost advantage, Professor McInnes makes the case for starting antihypertensive treatment with an ARB.